Manhattan Spur: Tracking the Far West Route of the Underground Railroad - Hermesch, Jessica (Kansas State University, The Chapman Center for Rural Studies, 2015)
Throughout the fall semester of 2014, Chapman Center intern, Jessica Hermesch, compiled information regarding the Underground Railroad through Pottawatomie County and Nemaha County, Kansas. Using copies of newspaper articles, online plat maps, research at the Onaga Historical Society (Pottawatomie County), interviews with local historians, and a wide variety of online and printed essays, an estimated route of travelers heading north from the far west point of the Underground Railroad (Manhattan, Kansas) was constructed. Multiple names and locations in Manhattan and the surrounding area have been confirmed as having been involved with the Underground Railroad. Names like Captain William Mitchell, the Beecher Bible and Rifle Company, Reverend Charles Emerson Blood, and Mount Mitchell are synonymous with this branch of the Lane Trail, the basis of Underground Railroad traffic through Kansas. Because specific names and locations like these have been confirmed in Manhattan, the main goal for this project was to focus on where people went between there and the town of Albany, in Nemaha County, Kansas. Albany was recorded as the most common last stop of Underground Railroad travelers before they left the state, but not much research had been conducted on how travelers of the Manhattan Spur got to the town.